2017
DOI: 10.21577/0100-4042.20170096
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an HPLC-DAD analytical method to quantify 5-methoxyflavones in methanolic extracts of Vochysia divergens Pohl cultured under stress conditions

Abstract: Vochysia divergens Pohl, known as "Cambara" in Brazil, is an invasive species that is expanding throughout Pantanal in Brazil, to form mono-dominant communities. This expansion is affecting the agricultural areas that support the typical seasonal flood and drought conditions of this biome. This article describes the development and validation of an HPLC-DAD analytical method to quantify 5-methoxyflavones in methanolic extracts of greenhouse-grown V. divergens associated with one of two endophytic fungal specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The VdE presents flavones in its chemical composition, being the flavone 3′5 DL its major component [9, 10]. Polyphenolic compounds, as flavones, can act as prooxidants in some in vitro systems [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VdE presents flavones in its chemical composition, being the flavone 3′5 DL its major component [9, 10]. Polyphenolic compounds, as flavones, can act as prooxidants in some in vitro systems [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pimenta et al [9, 10] demonstrated flavones as constituents of Vochysia extracts. Flavones are a class of flavonoids that are a subject of increasing interest because of their biological activities in vitro and in vivo , especially their antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants are the basis of our daily diet, providing primary‐metabolite nutrients such as carbohydrates, amino acids and lipids as well as a wide variety of secondary metabolites such as flavonoids, alkaloids, coumarins, terpenoids and steroids. Plant based metabolites have found widespread application in the agrochemical and pharmaceutical industries as well as food additives and flavours [1] . Secondary metabolites perform different roles in plant physiological processes and mediate their interactions with physical, chemical and biological agents, mainly by regulating the biochemical and molecular changes which the plant undergoes as a response to these stimuli [2] …”
Section: Introductionmentioning
confidence: 99%
“…Because the association of V. divergens with endophytic microorganisms is poorly understood, and since the chemical profile and biological potential of its microbiota remains partially unknown, our research group has been dedicated to the chemical study of this plant species (Pimenta et al, 2015) and its chemical interaction with its endophytic microbiota (Parpinelli et al, 2017;Pimenta et al, 2017;de Oliveira et al, 2018;Farias et al, 2019).…”
Section: Introductionmentioning
confidence: 99%